Kinetika Adsorpsi Ion Logam Cu+2 Menggunakan Tricalcium Phosphate Sebagai Adsorben - Siti Chotijah; Ahmad Fadli; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The methods used for reducing the level of heavy metals have been developed. One of the methods used for reducing the level of Cu metal wastes in waters is the adsorption process. The purpose of this research is to observe the effects of the initial Cu+2 metal ion concentration and the mass of the adsorbent on the capability of tricalcium phosphate (TCP) to adsorb, and also to establish a suitable model of the adsorption kinetics. Add a 500 mL solution of Cu (3 mg/L, 9 mg/L, and 15 mg/L) to tricalcium phosphate (TCP) (1 gram, 2 gram, and 3 gram) in a beaker glass, stirred with a speed of 300 rpm at 30oC. Take the solution of Cu2+ at 0; 30; 1; 1.5; 2; 2.5; 3; and 3.5 minutes, and then analyze the solution of dicentrifuge Cu and Cu by using the Atomic Absorption Spectroscopy (AAS). The research shows that the smaller the concentration of the adsorbent and the bigger the mass of the adsorbent, the bigger the capability of the Cu+2 metal ion to adsorb. The research also obtains the value of the kinetics, with a concentration of 3 mg/L, of 1 gram adsorbent (4.3721 g/mg.min), 2 gram adsorbent (5.4432 g/mg.min), and 3 gram adsorbent (5.4925 g/mg.min). With a concentration of 9 mg/L, 1 gram adsorbent (0.9926 g/mg.min), 2 gram adsorbent (1.1154 g/mg.min), and 3 gram adsorbent (1.4401 g/mg.min). With a concentration of 15 mg/L, 1 gram adsorbent (0.1390 g/mg.min), 2 gram adsorbent (0.2490 g/mg.min), and 3 gram adsorbent (0.4805 g/mg.min). The minimum value of the adsorption kinetics is obtained at 1 gram adsorbent with a concentration of 15 mg/L (0,1390 g/mg.min) and the maximum value of adsorption kinetics constants is obtained at 3 gram adsorbent with a concentration of 3 mg/L (5.4925 g/mg.min).Keyword : kinetic, adsorption, cuprum, tricalciumphosphate (TCP) .